PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU BULLYING PADA REMAJA DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATOR - Fety Indrawati; Rini Sugiarti (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Bullying is an aggressive behavior that is often found among school children, especially teenagers. One of the factors that influence bullying behavior is parental parenting. Another factor that plays a role in bullying behavior is the locus of control. The study aimed to analyze the influence of parental parenting on bullying behavior in adolescents moderated by the locus of control. The subjects in the study were 203 students at one of the private junior high schools in Kulon Progo, DIY. The sampling method used is total sampling. The data in this study was analyzed using the two ways analysis of variance (ANOVA) technique. Based on the results of data processing, there was a significant influence on parental parenting on bullying behavior, namely on authoritarian parenting and uninvolved parenting and also found no significant influence on locus of control on bullying behavior. There was also no significant influence on parental parenting on bullying behavior mediated by locus of control in adolescents. The implication of the study is that families, particularly parents, can use authoritative parenting patterns because they can encourage children not to engage in bullying behavior